FORECASTING THE READINESS TO PERFORM THE REPRODUCTIVE FUNCTION OF ADOLESCENT GIRLS - Kholova Nodira Fazliddinovna (Scholars Digest Publishing, 2023)
The purpose of the study is to predict the readiness to perform the reproductive function of adolescent girls. The survey was conducted according to the program for assessing the reproductive potential of girls and girls adapted to solve the set goal. Predicting the readiness of adolescent girls to perform the reproductive function and a comparative analysis of the realization of the reproductive potential of modern girls showed a negative trend in the main indicators of the reproductive function of young women, which is undoubtedly important for the subsequent prevention of reproductive losses in the form of targeted preparation of expectant mothers for a successful outcome of pregnancy and childbirth.
Keywords: reproductive health, reproductive system, puberty, reproductive function, adolescent girls.